2015
DOI: 10.1007/s10682-015-9759-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of timing of life history traits and population dynamic responses to climate change in spatially structured populations

Abstract: Changes in the seasonal timing of life history events are documented effects of climate change. We used a general model to study how dispersal and competitive interactions affect eco-evolutionary responses to changes in the temporal distribution of resources over the season. Specifically, we modeled adaptation of the timing of reproduction and population dynamic responses in two competing populations that disperse between two habitats characterized by an early and late resource peak. We investigated three scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In particular, up to 10 fold less chlorophyll a has been observed in Fidalgo Bay compared to the other sites. The proposed trade-off in energy allocation for this population could be driven by selection from such environmental differences in the quantity and timing of food supply 39 , 40 . As mentioned previously, selection could act through local adaptation or phenotype-environment mismatch, depending on the spatial scale of dispersal relative to the scale of environmental heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, up to 10 fold less chlorophyll a has been observed in Fidalgo Bay compared to the other sites. The proposed trade-off in energy allocation for this population could be driven by selection from such environmental differences in the quantity and timing of food supply 39 , 40 . As mentioned previously, selection could act through local adaptation or phenotype-environment mismatch, depending on the spatial scale of dispersal relative to the scale of environmental heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the factors contributing to gene flow necessitates a consideration of the factors contributing to dispersal, including the spatial structure of populations. Many theoretical studies assumed simple spatial structures like a linear environment (Andrade‐Restrepo et al 2019), two demes (Pontarp et al 2015), or populations structured as grid cells, with equal size and distance among them (Schiffers et al 2013). However, other experimental and theoretical studies with more complex spatial structure of populations have revealed that spatial structure has a major influence on demography, including potential consequences for metapopulation persistence (Vuilleumier et al 2007, Gilarranz and Bascompte 2012, De Roissart et al 2015), synchrony (Yeakel et al 2014, Larsen et al 2021), or metacommunity biodiversity (Carrara et al 2014).…”
Section: Introductionmentioning
confidence: 99%